Techno-Economic and Agricultural Best Practices for Increasing the Efficiency of Bioenergy Companies: Mixed Method for the Optimization of Land Use in Brazil and Australia - Carlucci, Fábio Vogelaar; Salgado Junior, Alexandre Pereira; Rebehy, Perla Calil Pongeluppe Wadhy; Lemos, Stella Vannucci [UNESP]; Novi, Juliana Chiaretti; Saddow, Stephen Edward (Wiley, 2025)
This study proposes techno-economic and agricultural best practices for increasing the efficiency of bioenergy companies. A mixed method was developed for increasing efficiency through the application of a two-stage data envelopment analysis (DEA), followed by a multiple case study. The efficiency concept model was based on the capacity of a sugarcane grower to maximize the production of sugarcane per planted area, while minimizing the generation of mineral and vegetable impurities. A multiple linear regression analysis was performed to identify the variables that exerted a major influence on the performance of the bioenergy companies. The quantitative approach developed here pointed to the identification of six variables that served as the basis for the qualitative stage of this research project. Through qualitative analysis, five other relevant variables were identified: cultivation activities, sugarcane renewal, edaphoclimatic factors, sugarcane genetic variety, and irrigation systems. Based on the identified variables, multiple case studies were conducted in Brazil and Australia to identify best practices that should yield superior results in terms of techno-economic and agricultural efficiency. One hundred best practices were identified and grouped according to the stages of the sugarcane production process and each category of technology, agricultural, and management practices. Most best practices were related to two specific stages of the sugarcane production process: (i) crop development and (ii) harvesting. Although Australia presented a greater concentration of best technology and agricultural practices, Brazil presented a greater concentration of best management practices, highlighting the potential and characteristics of each producing region. Thus, the results provide fundamental information for managers to make decisions and prioritize key factors that contribute most significantly to increasing the agricultural productivity of planted areas. Finally, as a practical contribution, a free online platform was developed for self-assessment of adherence to best practices by growers and an implementation methodology to increase efficiency in sugarcane production.
Keywords: agricultural best practices; bioenergy companies; mixed-method methodology; optimization of land use; renewable energy; two-stage DEA